2010
DOI: 10.1007/s13213-010-0135-z
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a novel extracellular carboxylesterase from the moderately halophilic bacterium Thalassobacillus sp. strain DF-E4

Abstract: An extracellular carboxylesterase from the moderately halophile Thalassobacillus sp. strain DF-E4 was purified to 8-fold with 11% recovery and specific activity of 2,046 U mg −1 . The molecular mass of the native enzyme was approximately 49 kDa as determined by analytical ultracentrifugation, while SDS-PAGE analysis showed a single protein band corresponding to a molecular mass of 45 kDa, suggesting that the enzyme was a monomer. Among the pNP (p-nitrophenyl) esters tested, p-nitrophenyl butyrate (C 4 ) was hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 41 publications
3
26
1
Order By: Relevance
“…As considering the B. cereus this was a novel characteristic and probably the first report on halotolerant esterase from B. cereus. This unique finding was comparable to the halotolerant esterase from halophiles [31,32] rather than other Bacillus sp. This verdict supported the opinions of Elend et al [33], stated that targeting habitat related characteristics, in many cases, leads to an underestimate of the enzyme's potential.…”
Section: Chemicalssupporting
confidence: 60%
See 1 more Smart Citation
“…As considering the B. cereus this was a novel characteristic and probably the first report on halotolerant esterase from B. cereus. This unique finding was comparable to the halotolerant esterase from halophiles [31,32] rather than other Bacillus sp. This verdict supported the opinions of Elend et al [33], stated that targeting habitat related characteristics, in many cases, leads to an underestimate of the enzyme's potential.…”
Section: Chemicalssupporting
confidence: 60%
“…The purified enzyme activity was almost inhibited by PMSF, which indicated that the purified esterase was serine enzyme. Besides, it was also strongly inhibited in the presence of PAO, a cysteine enzyme inhibitor [32], suggesting that serine and cysteine residues were essential for its catalytic activity. Moreover, the enzyme lost its full activity in the presence of reducing agent like DTT, 2-mercapto ethanol and urea, again in the presence of SDS, enzyme activity almost inhibited.…”
Section: Chemicalsmentioning
confidence: 99%
“…Complete inhibition of the b-amylase by DEPC, a histidine modifier [32], and PAO, a cysteine modifier [12], were observed, indicating that histidine and cysteine residues at the active site were essential for the enzyme catalysis. The activity was stimulated by Ca 2?…”
Section: Discussionmentioning
confidence: 99%
“…After incubation at 80°C for 2 h, about 40% activity still retained. In contrast, other halophilic esterases described previously were inactive under temperatures higher than 70°C [12,15]. Excellent thermostability may favor its application in processes that lead to inactivation of enzymes with increasing temperature.…”
Section: Discussionmentioning
confidence: 98%